Síndrome de Burnout en médicos del Hospital General Teófilo Dávila de Machala. - Sinchire Jiménez, Marlon Gabriel (2017)
Burnout Syndrome is a type of work stress that is observed in health professionals who maintain direct and constant contact with other people directly affecting the professional performance of the people and how they perceive the users. The general objective was to determine the prevalence of burnout syndrome in the physicians of the General Hospital Teófilo Dávila from Machala, to establish the dimension with more affectation, in addition to analyze Burnout syndrome in relation to gender, age, years of service in order to establish risk factors for physicians. A quantitative, descriptive and cross-sectional study was carried out in 119 physicians working in the institution, data collection was done through a survey that has a sociodemographic part and through the Maslach Burnout Inventory (MBI) questionnaire that evaluates the Dimensions of the syndrome. The present study identified a global prevalence of Burnout syndrome of 30.26% (n = 36); Has a higher percentage of presentation in the masculine gender 66.66% (n = 24), In the age of 20 to 30 years 36.17% (n = 13), this syndrome occurs most frequently in professionals working from 0 to 10 years old 58.34% (n = 21), Personal accomplishment was the most affected dimension 53.78% (n = 64), emotional fatigue 41.19% (n = 49) and depersonalization 47.05% (n = 56). In the group of resident physicians, a greater presentation of the syndrome was detected in comparison with treating physicians with 66.66% (n = 24). Keywords: Burnout Syndrome, Maslach Burnout Inventory, emotional exhaustion, Machala